Interfacial bonding controls friction in diamond–rock contacts - Bhamra,J; Ewen,J; Ayestaran,Latorre C; Bomidi,J; Bird,M; Dasgupta,N; van,Duin A; Dini,D (The Journal of Physical Chemistry C: Energy Conversion and Storage, Optical and Electronic Devices, Interfaces, Nanomaterials, and Hard Matter, 2021)
Understanding friction at diamond–rock interfaces is crucial to increase the energy efficiencyof drilling operations. Harder rocks usually are usually more difficult to drill; however, poorperformance is often observed for polycrystalline diamond compact (PDC) bits on soft calcitecontaining rocks, such as limestone. Using macroscale tribometer experiments with adiamond tip, we show that soft limestone rock (mostly calcite) gives much higher frictioncoefficients compared to hard granite (mostly quartz) in both humid air and aqueousenvironments. To uncover the physicochemical mechanisms that lead to higher kinetic frictionat the diamond–calcite interface, we employ nonequilibrium molecular dynamics simulations(NEMD) with newly developed Reactive Force Field (ReaxFF) parameters. In the NEMDsimulations, higher friction coefficients are observed for calcite than quartz when watermolecules are included at the diamond–rock interface. We show that the higher friction inwater-lubricated diamond–calcite than diamond–quartz interfaces is due to increasedinterfacial bonding in the former. For diamond–calcite, the interfacial bonds mostly formthrough chemisorbed water molecules trapped between the tip and the substrate, while mainlydirect tip-surface bonds form inside diamond–quartz contacts. For both rock types, the rate ofinterfacial bond formation increases exponentially with pressure, which is indicative of astress-augmented thermally activated process. The mean friction force is shown to be linearlydependant on the mean number of interfacial bonds during steady-state sliding. Theagreement between the friction behaviour observed in the NEMD simulations and tribometerexperiments suggests that interfacial bonding also controls diamond–rock friction at themacroscale. We anticipate that the improved fundamental understanding provided by thisstudy will assist in the development of bit materials and coatings to minimise friction byre